Is the establishment of MPAs enough to preserve endangered intertidal species? The case of Patella ferruginea in Mal di Ventre Island (W Sardinia, Italy). Issue 4 (7th August 2015) - Coppa, Stefania; De Lucia, G. Andrea; Massaro, Giorgio; Camedda, Andrea; Marra, Stefano; Magni, Paolo; Perilli, Angelo; Di Bitetto, Massimiliano; García‐Gómez, José Carlos; Espinosa, Free
Abstract: The giant limpet Patella ferruginea is the most endangered endemic species in the Mediterranean Sea. It is at serious risk of extinction, especially along the coast of Corsica and Italy. The small population of P . ferruginea in the marine protected area (MPA) Penisola del Sinis ‐ Isola di Mal di Ventre (W Sardinia, Italy) is an isolated unit whose preservation is critical also from the perspective of conservation genetics. This study considered the impact of illegal harvesting on the conservation status of P . ferruginea in the MPA. Site accessibility (semi‐accessible and hardly accessible) and legal protection (Zone A, B, C) were considered in two field surveys conducted in the Mal di Ventre Island in 2011 and 2013. Furthermore, Zone A was monitored annually from 2009 to 2013 to assess population dynamics and extinction risk. In summer 2013 the total population size was estimated at 310 specimens (0.016±0.005 ind m ‐1 ) with a significant decrease compared with 2011 (–52%), mainly due to poaching. Significantly higher density was found in the hardly accessible sites (0.039±0.007 ind m ‐1 in 2013) and generally in Zone A (0.042±0.009 ind m ‐1 in 2013). The size distribution showed a similar pattern, with larger sized individuals in those sites with maximum legal protection and a lower degree of accessibility. Juveniles (<25 mm) were almost absent and the mean individual growth rate (2.6±0.5 mm yr ‐1 ) was lower in comparison with other Mediterranean populations. The population viability analysis predicted that, with current rates of harvesting, P . ferruginea may face local extinction within the next 10 years. Without a joint effort towards the protection of intertidal habitats by enforcement bodies, regulators, researchers and sea users, the MPA will not achieve its conservation objectives and P . ferruginea will disappear from Mal di Ventre Island. Copyright © 2015 John Wiley & Sons, Ltd.